Cost‐Effective Synthesis of Electrodeposited NiCo2O4 Nanosheets with Induced Oxygen Vacancies: A Highly Efficient Electrode Material for Hybrid Supercapacitors. Issue 11 (4th August 2020) - Pappu, Samhita; Nanaji, Katchala; Mandati, Sreekanth; Rao, Tata N.; Martha, Surendra K.; Bulusu, Sarada V.
Abstract: Nanostructured transition metal oxide synthesis possessing high energy density and stability is desirable for supercapacitors. Herein, we synthesize three‐dimensional NiCo2 O4 (NCO) nanosheets with oxygen vacancies induced by sustainable and environmentally benign electrodeposition assisted chemical reduction process. Oxygen vacancies increase the conductivity, adsorptivity, and the active surface area, thereby enhancing the charge storage capabilities. The binder‐free NCO delivers the highest specific capacitance ( C sp ) of 2065 F g −1 at 1 A g −1, retaining 89.30 % of its initial value at 10 A g −1 after 10, 000 continuous charge‐discharge (CD) cycles. An asymmetric supercapacitor (ASC) fabricated shows remarkable electrochemical properties with high energy density ( E max ) of 28.6 Wh kg −1 and power density ( P max ) of 7.5 kW kg −1 . The assembled ASC reports exceptional cyclic retention of 90.6 % for 10, 000 CD cycles with practical demonstration. The approach used herein is suitable for eco‐friendly supercapacitor electrode fabrication with large scale manufacturing capability and less capital investment. Abstract : Incredible vacancies : Oxygen vacancies‐induced NiCo2 O4 nanosheets have been synthesized by facile and inexpensive electrodeposition followed by a chemical reduction route for hybrid asymmetric supercapacitor application, resulting in excellent electrochemical performances and practical demonstration, thereby paving the way for next‐generation energy storage devices.